Reversible potential-induced structural changes of alkanethiol monolayers on gold surfaces - Darwish, Nadim; Eggers, P.; Ciampi, S.; Zhang, Y.; Tong, Y.; Ye, S.; Paddon-Row, M.; Gooding, J. (Elsevier Inc., 2011)
Electrochemical impedance spectroscopy and in-situ IR spectroscopy were employed to investigate potential-induced structural changes, and associated ionic permeability, of alkanethiol self-assembled monolayers (SAMs) deposited on gold surfaces. SAMs terminated with hydroxyl or methyl groups were investigated. It is shown that both SAMs are highly permeable to ions once the dc potential is increased above a value of approximately + 500 mV vs Ag/AgCl in a 0.1 M HClO4 aqueous solution. At potentials more anodic than 500 mV, there exists a reversible change in the resistance and the capacitance of the SAMs. The change in the dielectric properties exhibits the same trend for both methyl and hydroxyl terminated SAMs and is accompanied with a structural change as confirmed using in-situ IR spectroscopy as a function of the applied potential. © 2011 Elsevier B.V.